Legal Analysis of the Reappointment of Former Convicted Village Head Based on the Policy of Extending the Term of Office of the Village Head - Arif Zainudin; Keri Pranata; Adi Tri Setiyo (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The election of village heads is a manifestation of local democracy that affirms the sovereignty of the village people in determining leadership at the most basic level of government. Changes in regulations through Law No. 3 of 2024 which extended the term of office of village heads from six years to eight years, as well as the birth of the Ministry of Home Affairs Circular Letter Number 100.3/4179/SJ, have juridical and sociological implications for the legitimacy of the village head position. One of the crucial issues is the reappointment of village heads who have been entangled in criminal acts, as in the case of the Sekapuk Village Head who was sentenced to five months in prison for embezzlement but was re-inaugurated and received an extension of office. This study uses normative legal methods with legislative and conceptual approaches to examine the suitability of these policies with democratic principles, the principles of clean governance, citizens' political rights, and public accountability. The results of the study show that although the circular provides administrative legal certainty and prevents a vacancy in village leadership, the policy creates a normative conflict between the restoration of the political rights of former convicts and the demands for the integrity of public office. This condition has the potential to reduce public trust in village government and weaken the principle of accountability. Therefore, a more comprehensive policy formulation is needed by including morality and integrity requirements for village heads whose positions are extended so that the principles of democracy and good village governance are guaranteed.